Flexible Electronics: High‐Performance Magnetic Sensorics for Printable and Flexible Electronics (Adv. Mater. 5/2015). (February 2015) - Karnaushenko, Daniil; Makarov, Denys; Stöber, Max; Karnaushenko, Dmitriy D.; Baunack, Stefan; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> High‐performance giant magnetoresistive (GMR) sensorics are realized by D. Karnaushenko, D. Makarov, and co‐workers on page 880. These devices are printed at predefined locations on flexible circuitry. The printed magnetosensors remain fully operational over the complete consumer temperature range and reveal a GMR up to 37% and a sensitivity of 0.93 T−1 at 130 mT. With these specifications, printed magnetoelectronics can be controlled using flexible active electronics for the realization of smart packaging and energy‐efficient switches. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>